Auditors' Understanding of Corporate Social Responsibility (CSR) in Audits - Rahman, Fauzi; Putri, Gina (Manunggal Halim Jaya, 2023)
This study explores auditors' understanding of Corporate Social Responsibility (CSR) in audit engagements, aiming to elucidate the complexities and challenges faced in evaluating CSR-related disclosures. The research investigates auditors' comprehension of CSR concepts, challenges encountered in auditing CSR disclosures, the influence of organizational culture, reliance on regulatory frameworks, and the necessity for continuous professional development. Utilizing a qualitative research approach, data was gathered through interviews and literature reviews. Findings reveal a spectrum of understanding among auditors, influenced by factors such as education, training, and organizational culture. Challenges in auditing CSR disclosures include the subjective nature of CSR reporting, lack of standardized frameworks, and difficulties in assessing reliability. Organizational culture significantly shapes auditors' approaches, with ethical cultures prioritizing CSR considerations. Auditors rely on regulatory frameworks, particularly International Standards on Auditing (ISAs), yet face challenges in their application to CSR assurance. Continuous professional development emerges as crucial for enhancing auditors' competencies in auditing CSR activities. This study contributes to understanding the dynamics of CSR auditing, highlighting the importance of addressing challenges and promoting a culture of accountability and sustainability within audit firms.